Nadzór nad rynkiem ubezpieczeniowym na przykładzie Polski i Stanów Zjednoczonych – model działania - Filipowska, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
Over the last few years, the financial market has been progressing rapidly in new technologies, products and international range, especially in the area of insurance. This against changing laws and policies, there arises a need to check the working model of supervision and its institutions, who is responsible and is it keeping up-to-date with events on the market. Then compare the model and special institutions to other countries. This article uses the United States since it is a large, mature and fast changing system. Poland may have less institutions than the United States, but that does not translate to a less functional system, it is important to check the rules present in the Polish control system and how strong they fare on the market.
Keywords: ubezpieczenia; regulacje; nadzór; Polska; USA